1995
DOI: 10.1093/infdis/172.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Virus Burden in Long-Term Survivors of Human Immunodeficiency Virus (HIV) Infection Is a Determinant of Anti-HIV CD8+ Lymphocyte Activity

Abstract: Persons infected with human immunodeficiency virus (HIV) for > 8 years were studied to delineate virologic and immunologic attributes of long-term survival. Whereas those with 300-700 CD4+ cells/microL often had circulating cytotoxic T lymphocytes (CTL) against HIV antigens, those with > 1000 CD4+ cells/microL did not. The subjects with > 1000 CD4+ cells/microL had low virus burden, low levels of Gag-specific CTL precursors, and minimal CD8+ cell activation. Overall, elevated levels of CD8+ cells, CD38 antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(77 citation statements)
references
References 34 publications
5
70
2
Order By: Relevance
“…These numbers are ϳ3-15 times the number previously estimated by enzyme-linked immunospot or tetramer analysis (18, 40, 47, 52-54). In some cases, this percent approaches the total number of CD3 ϩ CD38 ϩ T cells previously believed to be mostly due to bystander activation in infected patients (21). This study includes a unique cohort of LTNPs that has been infected Ͼ13 years, has strong proliferative responses to HIV Ags, and maintains plasma virus levels Ͻ50 copies/ml.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These numbers are ϳ3-15 times the number previously estimated by enzyme-linked immunospot or tetramer analysis (18, 40, 47, 52-54). In some cases, this percent approaches the total number of CD3 ϩ CD38 ϩ T cells previously believed to be mostly due to bystander activation in infected patients (21). This study includes a unique cohort of LTNPs that has been infected Ͼ13 years, has strong proliferative responses to HIV Ags, and maintains plasma virus levels Ͻ50 copies/ml.…”
Section: Discussionmentioning
confidence: 98%
“…It has previously been proposed that patients that maintain effective restriction of HIV replication do so because of greater HIV-specific CD8 ϩ T cell responses. However, previous studies have not consistently demonstrated a significant correlation between levels of plasma virus and CD8 ϩ T cell responses measured in vitro (7,8,10,21,37,55,56). It has been further suggested that significant correlations between plasma virus levels and measures of HIV-specific CD8 ϩ T cell responses were not detected because the assays used require in vitro stimulation, are poorly reproducible, or are not reliably quantitative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virus stocks were prepared from 24-h harvests of supernatants from CEM cells (CCRF-CEM) infected with virus derived from COS cells electroporated with plasmid pNL4-3 (39). The nonsyncytium-inducing CCR5-tropic molecular clone HIV-1 JR-CSF (JR-CSF) stocks were prepared from 24-h harvests of supernatants from stimulated PBMC infected with the supernatant of COS cells electroporated with plasmid pYKJR-CSF (40) and expanded in stimulated PBMC or in a cryopreserved pool of purified activated allogenic CD4 ϩ cells prepared as described in the literature (41). Briefly, allogenic CD4 ϩ cells from three normal donors were individually purified by capture in CD4 mAb-coated tissue culture flasks (Applied Immunosciences, Santa Clara, CA) and activated by stimulation with Ab to CD3 (OKT3; Ortho Biotech, Raritan, NJ) at 200 ng/ml and with rIL-2 (5000 U/ml) for 5 days.…”
Section: Hiv-1 Infection Of Scid-hu Mice and Postnatal Thymocytesmentioning
confidence: 99%
“…A strong antiviral cytotoxic activity has been shown to correlate timely with the clearance of viremia in primary infection [5,6]. Furthermore, Gag-specific T helper cell and CTL responses seem to correlate inversely with the viral load [7,8].…”
Section: Introductionmentioning
confidence: 99%